The great experiment how to make diverse democracies work - Mounk, Yascha (New York Penguin Press, 2022)
The Great Experiment by Yascha Mounk is a book that explores the challenge of making diverse democracies work in the 21st century. Mounk argues that never in history has a democracy succeeded in being both diverse and equal, treating members of many different ethnic or religious groups fairly. He examines how diverse societies have long suffered from the ills of domination, fragmentation, or structured anarchy, and how most people are now deeply pessimistic that different groups can integrate in harmony. He also draws on history, social psychology, and comparative politics to offer insights and hope for how to overcome these obstacles and create a world in which our ascriptive identities come to matter less. He calls this the greatest experiment of our time, and urges us not to give up on the prospects of building fair and thriving diverse democracies.
Includes bibliographical references and index.
Keywords: Democracy